Homofobia y su efecto en la salud mental de una joven de 20 años de la ciudad de Babahoyo - Cortez Jiménez, Denisse Arlhey (2023)
This case study examines the effect of homophobia on the mental health of a 20- year-old girl in the city of Babahoyo. The objective is to determine how homophobia influences the mental health of the patient. It focuses on the line of investigation of integral health and its physical, mental and social factors, as well as on the subline of sexuality, gender, society and culture Homophobia Homophobia is a controversial topic and of public interest worldwide. Homophobia can have a negative impact on people's mental health, which can lead to problems such as low self-esteem, which led to a mood disorder, Interviews and psychological tests were conducted to demonstrate the effects of homophobia on the young woman's mental health. The structure of the document includes an introduction, a development that addresses the justification, theoretical support, applied techniques, situations detected, proposes solutions, results obtained, conclusions, bibliographies and annexes. To improve their quality of life, 8 sessions were held, which was where their alteration was detected and cognitive techniques were used.